Physique assessment in youth sports for talent identification and development - Hume, P. A.; Stewart, A. D. (Best practice protocols for physique assessment in sport, 2017)
Kinanthropometry can be useful in youth sports for talent development and improving sports performance. We consider the relationship between structure (as measured by anthropometry), physiology, psychology and skill for talent identification and how using these factors in isolation may risk overlooking potential champions. There must be care in predicting future adult performances based on adolescent testing because of the varied stability of physical traits during growth, especially surrounding adolescence. Segment breadths remain stable in relation to stature throughout adolescence and can be used for predictive purposes; however, segment lengths are unstable and should not be used as prediction criteria in talent identification programmes. Proportionality can be an important self-selector for sports. We outline how to predict adult size and proportions from the growing child, how there can be optimal size and proportions for the ideal performance (morphological optimisation) in sport and how athletes can tailor soft tissue for maximum functional effectiveness by training, tapering, etc. (morphological prototype). We examine how performance might be enhanced or retarded by biological maturity and how biological maturity is affected by energy balance in the young athlete—delaying maturation in some groups. Early maturers are often taller, heavier, more powerful and faster than their counterparts during the early to mid-teenage years, which has often led to selection biases in sporting competitions grouped by chronological age. Coaches need to consider anthropometric characteristics to avoid biasing their athlete selection.